PENGARUH MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, AND SHARE (SSCS) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA/MA PADA MATERI SISTEM EKSKRESI - Nova Ramadhani; Sa`diatul Fuadiyah (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
Critical thinking ability refers to the ability to analyze, evaluate, and solve problems. The purpose of this study was to determine the effect of applying the Search, Solve, Create, And Share (SSCS) learning model on students' critical thinking skills. This type of research is a quasi-experimental research with research methods using Nonequivalent Post Control Group Design. Sampling was carried out by purposive sampling technique, namely class XI IPA 3 and class XI IPA 4 as the control class using the direct learning model. The assessment was carried out on students' critical thinking skills using a written test in the form of multiple choices. From the results of the study, it was found that the critical thinking skills of students in the experimental class had an average of 76.74 with critical criteria, and so on the control class obtained an average of 63.95 with critical criteria. After testing the hypothesis with the t test, the result is that the value of tcount > ttable is 4.7194 > 1.667 which shows that the hypothesis is accepted. Based on the results of the study it was concluded that the application of the Search, Solve, Create, And Share (SSCS) model had a positive effect on the critical thinking skills of students of class XI IPA MAN 2 Padang